Walking corpses : leprosy in Byzantium and the medieval West - Miller, Timothy S., 1945-; Nesbitt, John W. (Cornell University Press, 2023)
"The history of leprosy in the West is incomplete without also considering the Byzantine Empire, which confronted leprosy and its effects well before the Latin West. The authors argue that ethical writings from the Byzantine world and from Catholic Europe never branded leprosy as punishment for sin; rather, theologians and moralists saw the disease as a mark of God's favor on those chosen for heaven"--